LncRNA, PLXDC2-OT Promoted the Osteogenesis Potentials of MSCs by Inhibiting the Deacetylation Function of RBM6/SIRT7 Complex and OSX Specific Isoform. (8th March 2021) - Liu, Huina; Hu, Lei; Yu, Guoxia; Yang, Haoqing; Cao, Yangyang; Wang, Songlin; Fan, Zhipeng
Abstract: Bone regeneration and remodeling are complex physiological processes that are regulated by key transcription factors. Understanding the regulatory mechanism of key transcription factors on the osteogenic differentiation of mesenchymal stem cells (MSCs) is a key issue for successful bone regeneration and remodeling. In the present study, we investigated the regulatory mechanism of the histone deacetylase Sirtuin 7 (SIRT7) on the key transcription factor OSX and osteogenesis of MSCs. In this study, we found that SIRT7 knockdown increased ALP activity and in vitro mineralization and promoted the expression of the osteogenic differentiation markers DSPP, DMP1, BSP, OCN, and the key transcription factor OSX in MSCs. In addition, SIRT7 could associate with RNA binding motif protein 6 (RBM6) to form a protein complex. Moreover, RBM6 inhibited ALP activity, the expression of DSPP, DMP1, BSP, OCN, and OSX in MSCs, and the osteogenesis of MSCs in vivo. Then, the SIRT7/RBM6 protein complex was shown to downregulate the level of H3K18Ac in the OSX promoter by recruiting SIRT7 to the OSX promoter and inhibiting the expression of OSX isoforms 1 and 2. Furthermore, lncRNA PLXDC2-OT could associate with the SIRT7/RBM6 protein complex to diminish its binding and deacetylation function in the OSX promoter and its inhibitory function on OSX isoforms 1 and 2 and to promote the osteogenic potential of MSCs. : Liu et al show that RNA binding motif protein 6 (RBM6) associate with Sirtuin 7 (SIRT7), promote the recruitment and deacetylase function of SIRT7 in the OSX proximal promoter, facilitating SIRT7 inhibition of OSX isoforms 1 and 2 and osteogenesis potential of mesenchymal stem cells (MSCs). LncRNA, PLXDC2-OT associate with the SIRT7/RBM6 protein complex for diminishing its binding and deacetylation function of OSX, and promote the osteogenesis of MSCs.